Analysis Of The Effect Of Chat GPT In Increasing Student Engagement In Blended Learning - Alfian, Ade; Risaldi, Dedi; Ummul Khaeri Masna; Nurrahmah Agusnaya (Jurnal MediaTIK, 2025)
Technological developments are bringing fundamental changes to education in Indonesia. The use of portable devices such as smartphones and tablets, along with widespread internet access, has enabled students and educators to adopt technology, including ChatGPT, as an advanced learning tool. E-learning, especially the blended learning model that combines face-to-face and online learning, provides time and place flexibility for learners. In this context, ChatGPT is used as a learning assistant that can respond to students' questions and provide clearer explanations. This study, focusing on students' response to blended learning e-learning, used quantitative method with questionnaire as data collection tool. The findings showed that the use of ChatGPT as a learning assistant in the context of blended learning had a positive impact on student engagement. The majority of respondents stated that interaction with ChatGPT improved their understanding of learning materials and helped them overcome learning obstacles independently. The flexibility of time and place in e-learning is also a determining factor in the success of this blended learning model. Students considered that being able to access learning materials anytime and anywhere through their portable devices improved learning efficiency.